The anti-anemic effect of dried beet green in phenylhydrazine treated rats - Shahenda M. Elaby; Jehan B. Ali (Ain Shams University, 2018)
Phenylhydrazine (PHZ) and its derivatives were used firstly as antipyretics but the toxic action on red blood cells made their use dangerous. The aim of this study was to estimate the contents of iron and vitamins in different parts of beetroot as root and beet green (leave and stalk together) as well as their ethanol extracts. Then, the biochemical evaluation for the highest iron and vitamins contents as an anti-anemic effect against anemic rats caused by phenylhydrazine were studied. Anemia induction caused by intraperitoneal injection of phenylhydrazine at 40 mg/kg for 2 days. Rats were randomly divided into four groups (n=10/group). Group, I fed a standard diet (normal control). Group II fed standard diet contained 5% dried beet green for normal rats. Group III fed a standard diet for anemic rats. Group IV fed a standard diet containing 5% dried beet green for anemic rats. It was assayed the complete blood count (CBC): red blood cell (RBC) count, hemoglobin concentration (Hb) and haematocrit percentage (HCT) as indices measured of anaemia as well as white blood cell (WBC) count at the third day (D3), twenty-one day (D21) and forty-two day (D42). Also, the activity of serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), the levels of serum urea, uric acid, creatinine and malondialdehyde (MDA), plasma hydrogen peroxide (H2O2) and total antioxidants capacity (TAC) contents were analyzed according to manufacturer's instructions. The dried beet green is a rich source of iron and vitamins contents. After feeding on standard diet containing 5% dried beet green for anemic rats, showed that levels of RBC, HB and HCT were increased and the WBC count was improved compared to anemic control group. The activity of ALT, AST, and ALP, the levels of serum urea, creatinine and MDA and plasma H2O2 content were significantly ameliorated while the TAC was significantly increased compared to the anemic control group. In addition, the results of the histological examination coincided with the results of blood analysis. We conclude that nutrition of 5% dried beet green for forty-two days is safe, non-toxic and reduces anemia.